Pengembangan Sistem Informasi E-Tourism sebagai Media Pemasaran (Studi Kasus Kabupaten Trenggalek) - Asroru Maula Romadlon; Issa Arwani; Dian Eka Ratnawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Department of Tourism and Culture (DISPARBUD) of Trenggalek Regency is a government agency authorized in terms of tourism. There are various fields that exist in the Trenggalek Regency DISPARBUD, one of which is the marketing field which is responsible for marketing or tourism promotion. DISPARBUD wants to add to its tourism marketing method that does not currently exist with the desire to create a mobile application that can provide information to tourists about tourism objects in Trenggalek Regency. With these problems, DISPARBUD offered to develop an E-Tourism information system. System development in the form of a web application for admins that can be used to view, add, change, and delete tourism object data, as well as a mobile application in the form of Android which will be used by users to access tourism information. The development of the E-Tourism information system was developed using the waterfall method. This system utilizes an API so that the web admin application and the user's mobile application can be connected to each other. Then testing is carried out starting from API testing which results in the API being able to run and being accessed by the user's mobile application, black box testing with validation testing which shows that all functional requirements of the system have been met, compatibility testing shows that web admin applications can be run on different browsers and mobile applications can be run. on different android versions, as well as usability testing with the SUS (System Usability Scale) test which shows this system has received acceptable criteria in the acceptable range and got a B grade scale.